Safety Evaluation for Restorin® NMN, a NAD+ Precursor - Turner, John; Licollari, Albert; Mihalcea, Emil; Tan, Aimin (Frontiers in Pharmacology, 2021)
NAD+ is the most abundant molecule in the body besides water and vital to all living cells. NAD+ levels decline with age, and this decline correlates with age-related diseases. Therefore, sustaining NAD+ levels offers potential benefits to healthspan and longevity. Here we conducted toxicity studies to evaluate the safety of Restorin® NMN, a high purity form of the NAD+ precursor, β-nicotinamide mononucleotide (NMN). Based on the acute toxicity study and a 14-day repeated dose toxicity study, Restorin® NMN was administered orally to Sprague-Dawley rats for 91 days followed by a 14-day recovery period. The oral doses of 500, 1000, and 2000 mg/kg/day were compared. There were no test item-related findings that could be considered adverse events in animals dosed at 500 mg/kg/day. The findings in the Restorin® NMN high dose group (2000 mg/kg/day) were similar to the reference item (Nicotinamide Riboside Chloride) dosed at 1740 mg/kg/day: reduction in body weight, body weight gains, and food consumption. In conclusion, the No-Observed-Adverse-Effect-Level (NOAEL) for NMN is 1000 mg/kg/day in female rats and 500 mg/kg/day in male rats, and the Low-Observed-Adverse-Effect-Level (LOAEL) for NMN is 2000 mg/kg/day.